Intensifikasi Produksi Konten sebagai Strategi Promosi Film di PT Sinemart Indonesia - Fasya Hazhiyah; Willy Bachtiar (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
This study aims to examine how content production intensification is utilized to optimize social media algorithms as a film promotion strategy at PT Sinemart Indonesia. The research employed a descriptive qualitative approach, with data collected through observation, semi-structured interviews, and documentation. Four informants were selected using purposive sampling techniques. Data collection was conducted during an internship period from January 27 to May 10, 2026. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, while source triangulation was applied to ensure the validity of the findings. The results indicate that PT Sinemart Indonesia implements a content intensification strategy by publishing approximately 20 promotional posts per day to maximize algorithmic content distribution opportunities. This strategy is supported by Agenda Setting Theory, which views algorithms as new digital gatekeepers in determining information visibility, Uses and Gratifications Theory, which explains audience engagement based on entertainment and social connectivity needs, and Integrated Marketing Communication (IMC), which emphasizes message consistency across multiple platforms. Beyond content quantity, the study also found that message relevance and platform-specific content adaptation play crucial roles in enhancing promotional effectiveness. The mirroring approach between TikTok and Instagram was considered less effective because it limits optimal algorithmic reach and broader audience engagement.